Evaluation of an alternative technique for preserving crustaceans in dry conditions with joint mobility: a proposal for didactic purposes - Amanda Brito Costa; Márcio Borba da Silva; Ricardo Evangelista Fraga; Agda Alves da Rocha; Patrícia Belini Nishiyama; Matheus Santos dos Anjos; Joaquim Jorge Silveira Buchaim; Mariane Amorim Rocha (Acta Scientiarum: Biological Sciences, 2021)
Although crustaceans are traditionally preserved in liquids (formaldehyde and/or ethyl alcohol), those substances tend to alter their morphological aspects. Glycerin, used in human anatomy, is considered a good substitute for formaldehyde, as it preserves animals in states similar to in vivo conditions. There are no records in the literature, however, concerning the use of glycerin for conserving invertebrates. The objective of this work was to elaborate and evaluate alternative techniques for conserving the crustacean Ucides cordatus (Linnaeus, 1763). Six fixatives (1, 3, 4 and 5% formaldehyde, 70% alcohol, and dietrich solution) and two controls (positive and negative) were tested, as well as the effects of freezing before fixation on the integrity of U. cordatus specimens. Our results were evaluated with respect to nine variables. The treatments that demonstrated the best aesthetic results were 4% formaldehyde and 70% ethyl alcohol. The freezing of the animals resulted in brittle organs in all treatments tested. The technique discussed here is extremely promising for the conservation of animals for educational purposes, as it produces preserved specimens that are aesthetically similar to their in vivo conditions.